DAMPAK KEBIJAKAN MONETER PEMULIHAN EKONOMI NASIONAL TERHADAP KINERJA PERBANKAN DI INDONESIA - Candra Asih, Putri Galuh; Syafitri, Wildan (Journal of Development Economic and Social Studies, 2023)
This study aims to describe how the monetary policy of national economic recovery affects the performance of banks that mediate the running of that policy. This research data uses secondary data in the form of a combination of crossection and time series data also limited by the research time starting from the first quarter of 2020 to the fourth quarter of 2022. The data taken are ROA, BI-7DRR, lending, and credit restructuring. The analysis method used is panel data regression where the model used is random effect. The findings of this study indicate that the monetary policy of national economic recovery is effective in minimizing the impact of COVID-19 on banking performance. After this policy is implemented, changes in the value of lending, credit restructuring, and BI-7DRR minimize the decline in bank profitability in the face of the COVID-19 pandemic. However, when viewed individually, the BI-7DRR instrument shows a negative influence on bank profitability where the decline in BI-7DRR makes bank profitability increase.